Exploring the Meaning of the Arabic Song Lyrics ’Nour El Ein’ by Amr Diab (A Semiotic Review of Riffaterre) - Dzakirah, Dzakiyyah Jilan; Ramadhan, Ilham; Haeriyyah, Haeriyyah; Agussalim, Andi; Ahmad, Muhammad Anwar bin (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
The lyrics of songs are often enigmatic and difficult to understand, requiring deeper interpretation to uncover hidden meanings. This is especially true for the lyrics of "Nour El Ain" by Amr Diab, which contain phrases such as "the light of my eyes," "your heart calls me," "the magic of your eyes," and "You live in my dreams." Given the depth of meaning contained in these lyrics, this research is important, as they convey feelings of love, longing, and hope. This study employs the semiotic approach of Michael Riffaterre to analyze the meanings within the lyrics. Riffaterre emphasizes that elements of poetry possess dual meanings that can be revealed through deeper analysis, allowing for a richer understanding of the emotions and themes contained in the song. The aim of this research is to interpret the meaning of the lyrics of "Nour El Ain," with the expectation of providing a deeper understanding through explanations of the indirectness of expression, heuristic readings, hermeneutic readings, matrices, models, variants, and hypograms, which represent stages of understanding poetry in Riffaterre’s semiotics. The methodology used is descriptive-qualitative, and the findings include substitution and distortion of meaning, as well as the creation of meaning through rhyme and symbolism, heuristic readings presenting love as a source of happiness, hermeneutic readings demonstrating deep love and unwavering commitment, matrices reflecting transcendent love, and hypograms divided into potential and actual types. مستخلص تُعتبر كلمات الأغاني غالبًا غامضة وصعبة الفهم، وتتطلب تفسيرًا أعمق لاكتشاف المعاني الخفية. وهذا ينطبق بشكل خاص على كلمات أغنية "نور العين" لعمر دياب، التي تحتوي على عبارات مثل "نور عيني"، "قلبك يناديني"، "سحر عينيك"، و"تعيش في أحلامي". نظرًا لعمق المعاني الموجودة في هذه الكلمات، فإن هذا البحث مهم، حيث تعبر عن مشاعر الحب والحنين والأمل. يستخدم هذا البحث المنهج السيميائي لمايكل ريفاتير لتحليل المعاني ضمن الكلمات. يؤكد ريفاتير على أن عناصر الشعر تحمل معاني مزدوجة يمكن كشفها من خلال تحليل أعمق، مما يسمح بفهم أغنى للعواطف والمواضيع الموجودة في الأغنية. الهدف من هذا البحث هو تفسير معنى كلمات "نور العين"، مع توقع تقديم فهم أعمق من خلال توضيحات غير مباشرة، وقراءات استكشافية، وقراءات تأويلية، ومصفوفات، ونماذج، ومتغيرات، وهي تمثل مراحل فهم الشعر في سيميائيات ريفاتير. المنهج المستخدم هو وصفي-نوعي، وتشمل النتائج استبدال وتحريف المعنى، بالإضافة إلى خلق المعنى من خلال القافية والرمزية، حيث تقدم القراءات الاستكشافية الحب كمصدر للسعادة، وتظهر القراءات التأويلية الحب العميق والالتزام الثابت، وتعكس المصفوفات الحب المتعالي، وتقسم الهيبوجرامات إلى أنواع محتملة وواقعية.